2019
DOI: 10.1128/jb.00061-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Ionic Strength Tolerance between Freshwater and Marine Caulobacterales Adhesins

Abstract: Bacterial adhesion is affected by environmental factors, such as ionic strength, pH, temperature, and shear forces. Therefore, marine bacteria must have developed adhesins with different compositions and structures than those of their freshwater counterparts to adapt to their natural environment. The dimorphic alphaproteobacterium Hirschia baltica is a marine budding bacterium in the clade Caulobacterales. H. baltica uses a polar adhesin, the holdfast, located at the cell pole opposite the reproductive stalk, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…It must be considered that beside the similar pH values of freshwater and seawater, the ionic strength may be different. Due to a higher amount of solved salts in seawater, the ionic strength is described to be 500 times higher than in freshwater [59]. As soon as the polymers face either freshwater or seawater, their surfaces may interact with available ions, influencing their ζ-potential immediately.…”
Section: Correlation Of Structural Diversity Of Early-stage Biofilms and Polymer Propertiesmentioning
confidence: 99%
“…It must be considered that beside the similar pH values of freshwater and seawater, the ionic strength may be different. Due to a higher amount of solved salts in seawater, the ionic strength is described to be 500 times higher than in freshwater [59]. As soon as the polymers face either freshwater or seawater, their surfaces may interact with available ions, influencing their ζ-potential immediately.…”
Section: Correlation Of Structural Diversity Of Early-stage Biofilms and Polymer Propertiesmentioning
confidence: 99%
“…Hentchel et al (2019) grew axenic cultures of C. crescentus in complex and chemically defined media to examine the fitness of transposon mutants in freshwater environments and described a new model system to study gene function in ecosystems. In a comparison of the physicochemical properties of adherence between freshwater and marine Caulobacterales, Chepkwony, Berne, and Brun (2019) found the marine Hirschia baltica maximized binding via their holdfast in environments with high ionic strength. Caulobacter crescentus shifts cell morphology in response to changing growth conditions (Heinrich, Leslie, Morlock, Bertilsson, & Jonas, 2019).…”
Section: Bacterial Ecologymentioning
confidence: 99%
“…Previous atomic force microscopy (AFM)-based studies revealed that the bacteria–GO interaction was predominantly repulsive due to the electrostatic and steric repulsion between deprotonated carboxylate groups in GO and the negatively charged cell surface. , On the other hand, the enhanced bacterial attachment to GO-coated organic and inorganic surfaces via hydrophobic interaction has been demonstrated. These contradictory conclusions are mainly derived from the various parameters influencing the interfacial behaviors. It has been recognized that the chemical properties of the background electrolyte such as ionic strength govern the extent and mechanisms of bacterial attachment to surfaces. Moreover, the lack of real-time and quantitative analysis of the bacterial deposition dynamics on GO surface also leads to divergent results from different investigators. ,, As bacterial attachment onto GO is critical in determining GO’s antibiofouling and antibacterial performance, it is crucial to reveal the effect of solution chemistry on the dynamic bacterial attachment processes on GO surface and develop a comprehensive understanding of bacteria–GO interaction.…”
Section: Introductionmentioning
confidence: 99%